Viral abundance and diversity vary with depth in a southeastern United States agricultural ultisol. (October 2019) - Liang, Xiaolong; Wagner, Regan E.; Zhuang, Jie; DeBruyn, Jennifer M.; Wilhelm, Steven W.; Liu, Fang; Yang, Lu; Staton, Margaret E.; Sherfy, Andrew C.; Radosevich, Mark
Abstract: Viruses shape microbial communities and associated processes across ecosystems. However, soil viral ecology remains poorly understood, and in particular, the vertical distribution and diversity of viruses and virus-host interactions in soils remain underexplored. In this study, 16S rRNA gene amplicon and virome sequencing were applied to investigate bacterial and viral diversity and provide insight on virus-bacterium interactions in different depths of soil profiles. The results show that bacterial community composition varied with soil depth, driven by an increase in the relative abundance of Chloroflexi and a decline in the relative abundance of Planctomycetes, Proteobacteria, Verrucomicrobia, Actinobacteria, and Acidobacteria. Additionally, landscape position, depth, and virus abundance had the strongest correlation with the bacterial community structure. Virus abundance decreased with soil depth, and bacterial community diversity correlated positively with viral abundance ( P < 0.001). Viruses of prokaryotes were most prevalent in the viromes of both surface and subsurface soils relative to the total viruses detected, however the relative abundance of bacteriophages was greater in the subsurface than in the surface soil. Viral abundances showed significant correlations (negative/positive) with many bacterial taxa in soil, suggesting possible ecological interactions between viruses and specific bacterial taxa. Auxiliary metabolic genes (AMGs, e.g., genes of oxidative phosphorylation, cell signaling, and nucleotide, amino acids, and carbohydrates metabolisms) were detected in viromes (surface: 2359 AMGs with 35.7% coding percentage; subsurface: 8150 AMGs with 87.1% coding percentage). The abundances of AMGs were up to 16-fold higher in subsurface than in the surface viromes. The results showed that soil viruses are diverse and have potential to modulate host metabolism and community structure. Highlights: Viral abundance decreased with soil depth. Viral abundance was correlated with bacterial community diversity in soil. Subsurface virome was dominated by prokaryotic viruses. Giant viruses were present in surface but absent in subsurface viromes. Subsurface soil viruses had a greater normalized abundance of functional genes.